The Missing Link: The Ricardian Approach to the Factor Endowments Theory of Trade - Ruffin, Roy J. (American Economic Review, 1988)
[This paper views all interpersonal exchange as Ricardian, while all international trade reflects each country's factor endowment. The model provides the logical link between Heckscher-Ohlin and Ricardo. The strength of the model is that it allows simpler and more robust theorems about trade, welfare, and factor payments. For example, factor price equalization is universal and the old Mill-Ricardo theorem that the small country gains all from trade is incorrect.]